Seed transmission of Ascochyta rabiei, the causal organism of chickpea blight - MAHENDRA PAL, PREMJIT SINGH and (Indian Phytopathology, 2002)
Disease transmission studies conducted under in vitro conditions revealed various kinds of infection that spread from chickpea seed to seedling, although infected seeds did not always produce infected seedlings. Lesions of the fungus often developed on the seed but coleoptile and coleorhiza remained free from infection. In other cases infection spread from the lesion either to the coleoptile or to the coleorhiza or to both. In pot experiments the disease was transmitted from the infected seed to the seedling at a rate of 6.1%.